Lessons Learned in Interfacial Tension Prediction Using a Mixture of Sulfonate- and Ethoxylate-based Surfactants in a Waxy Oil-brine System - Rani Kurnia; Dian Asfriany Nurfalah; Deana Wahyuningrum; Taufan Marhaendrajana; Utjok W.R Siagian (Journal of Engineering and Technological Sciences, 2023)
The chemical-enhanced oil recovery (CEOR) method is applied to change reservoir rock or fluid characteristics by injecting alkaline, surfactant, and polymer or a combination of two or three of the compounds. Surfactant flooding improves oil recovery by reducing the interfacial tension between oil and water. Selecting reservoir surfactants, especially microemulsions, requires careful screening. This study predicted waxy oil system interfacial tension using surfactant mixtures at below- and above-optimum salinity. To predict the interfacial tension, microemulsion types, HLB, ideal salinity, and HLD were used. The study predicted oil-surfactant-water interfacial tension using SAE, FEO, and their mixtures. We improved the Huh equation by adding a fitting parameter, β, to accommodate the transition from type III to type II microemulsions as salinity increases. With increasing salinity, anionic surfactant’s hydrophilic-hydrophobic interactions change, affecting the  values and surfactant layer thickness. This study improved hydrophilic-lipophilic deviation (HLDN) by establishing a fixed interval for nonionic surfactants. Van der Waals attraction,  values and interface surfactant layer thickness are connected, reflecting the fact that lower  values reduce interfacial tension better. This study also found that surfactant packing at the oil-water interface increases the order of the oil-solution ratio and the microemulsion values with polarity.